2010
DOI: 10.3171/2009.9.spine09407
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin for prevention of epineurial fibrosis in a rat sciatic nerve model: outcome based on gross postsurgical, histopathological, and ultrastructural findings

Abstract: The results of gross postsurgical anatomical evaluation and histopathological and ultrastructural studies suggested that topical application of DXR effectively reduced epineural scar formation on rat sciatic nerves. These promising findings merit further experimental and clinical studies to determine the efficacy and safe applicability of DXR in human subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Postoperative perineural scarring and adhesion are inevitable, even when using meticulous surgical techniques, including microsurgical techniques. Several pharmacologic agents reduce scar formation in peripheral nerve surgery, including cis-hydroxyproline,22) anti-transforming growth factor-β1 antibody,23) citicoline,24) ADCON-T/N,16) and doxorubicin 25). All these drugs may have positive effects in experimental studies, but they have not yet been applied clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative perineural scarring and adhesion are inevitable, even when using meticulous surgical techniques, including microsurgical techniques. Several pharmacologic agents reduce scar formation in peripheral nerve surgery, including cis-hydroxyproline,22) anti-transforming growth factor-β1 antibody,23) citicoline,24) ADCON-T/N,16) and doxorubicin 25). All these drugs may have positive effects in experimental studies, but they have not yet been applied clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological and histopathological results were consistent and parallel in both groups. The results were summarized in Table III. dISCuSSIon Peripheral nerve trauma, with an estimated incidence of 1/1000 in population per year, remains a major cause of morbidity and social disruption (4 (2,6,7,8,23,24,25,26,37). To the best of our knowledge no study has been reported on preventing intraneural scarring by radiation.…”
Section: Latency Measurementsmentioning
confidence: 92%
“…Improvements in our understanding of biocompatibility during device manufacture along with continuing improvement in surgical techniques has dramatically reduced the prevalence of significant immune-mediated peripheral nerve damage consequent to implantation of cuff electrodes [22]. Current efforts are directed at further reducing the inflammatory response in hopes of minimizing the possibility of electrical damage secondary to increased current required to stimulate nerve fibers through additional fibrous tissue [23,24].…”
Section: Inflammatory Nerve Injurymentioning
confidence: 99%